Diagnosis of Impairments in the Hemostatic System in the Use of Warfarin in Cardiac Surgical Patients - E. I. Goncharova; E. A. Spiridonova; A. N. Balandina; A. V. Poletaev; A. M. Sepoyan; F. I. Ataullakhanov; S. A. Rumyantsev; N. N. Samsonova; L. G. Klimovich; E. A. Kornienko (Общая реаниматология, 2015)
Objective: to reveal early changes in the hemostatic system during warfarin therapy in cardiac surgical patients, by comprehensively evaluating their hemostatic status.Subjects and methods. Seventyfive patients receiving cardiac surgical treatment were examined. All the patients took warfarin for 5±1.5 days. Laboratory studies involving the determination of routine coagulogram readings and thrombodynamic indicators (lag time (Tlag) and rate (Vs) of clot growth, and concentrations of individual Factors II, VI, IX, and X) were used to evaluate the patients' hemostatic status.Results. 28% of the patients were found to have an international normalized ratio (INR) of above 3.0. There was a correlation of Tlag with INR (R2=0.66). Both indicators were  comparatively highly correlated with Factor II and Factor X concentrations (R2=0.50 and 0.40 for Tlag; R2=0.53 and 0.48 for INR) and were uncorrelated with Factor IX levels (R2=0.20 for Tlag and 0.34 for INR). However, there was a difference in Factor VII concentrations: no correlation for Tlag (R2=0.20) whereas it for INR was rather high (R2=0.42). The index Vs was uncorrelated with INR (R2=0.24) and the concentration of blood coagulation factors (R2<0.1). There was a high correlation between Factor II and Factor X concentrations (R2=0.87); the correlation between the concentrations of all other pairs of coagulation factors was substantially lower (R20.45). The lack of correlation of a thrombodynamic indicator, such as clot growth rate, with the concentration of coagulation factors points to the fact that warfarin acts mainly on the phase of coagulation activation rather than that of clot propagation.Conclusion. The weak correlation between coagulation factors (except that of a pair of Factor II and Factor X) is indicative of the individual response of the patients to warfarin treatment and the need to monitor the hemostatic status by global hemostatic tests rather than by individual proteins. The thrombodynamic indicator Tlag reflects the effect of warfarin in proportion to INR. Warfarin virtually fails to affect the rate of clot growth so this indicator may be used to evaluate the patient's procoagulant status uncompensated for with warfarin intake.